UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN BIOLOGI MELALUI MODEL PEMBELAJARAN KUIS KARTU BERVARIASI PADA SISWA KELAS XI.IPA.4 IPA 4 SMAN 1 KINALI - Erda Wati (JURNAL MANAJEMEN PENDIDIKAN, 2018)
Abstract Based on the learning outcomes of students of class XI.IPA.4 SMAN 1 Kinali in Biology sub Subject Describes the structure and function of certain human and animal organs, abnormalities or diseases that may occur and the implications found that the students' learning outcomes in the subjects Biology sub Describes the structure and function certain human organs, possible abnormalities or diseases and their implications are still very low. The average student learning outcomes are still under the KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in the subjects Biology sub Describes the structure and function of certain human and animal organs, abnormalities or diseases that may occur as well as the implications through the model of Various Card Quiz Learning in class XI.IPA. 4 SMAN 1 Kinali West Pasaman District. This research is a classroom action research. The research procedures in this research include planning, action, observation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 33 students of class XI.IPA.4 SMAN 1 Kinali. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that the learning model Card Quiz Bervariasi can improve student learning outcomes in the subjects Biology Sub Writing Text Speech / lecture / sermons with systematic and effective language in SMAN 1 Kinali. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 53.52 (Less) increased to 83.24 (good) with an increase of 29.72.Keywords: Learning Outcomes, Biology, Varied Card Quiz learning model